BIM in small practices : illustrated case studies - Klaschka, Robert (NBS, 2014)
"BIM (Building Information Modelling) is revolutionising architecture and construction, as more and more practices are realising the benefits it brings to design, sustainability, and construction. There is a perception that BIM is a process best left to large practices requiring significant resources and the ability to invest heavily in IT. This book overturns that misconception: introducing a selection of inspirational BIM-enabled projects by small architectural practices. Full of practical tips and hard-won experience, BIM in Small Practices: Illustrated Case Studies includes pithy contributions from industry experts who identify and explore the important issues for small practices including how to get your practice started with BIM, and how it aligns to the new Plan of Work. This landmark publication will motivate small practices who are considering taking those first steps towards implementing BIM."--Back cover